A risk management model for familial breast cancer: A new application using Fuzzy Cognitive Map method. Issue 2 (November 2015) - Papageorgiou, Elpiniki I.; Jayashree Subramanian; Karmegam, Akila; Papandrianos, Nikolaos
Highlights Development of a familial breast cancer risk assessment model using Fuzzy Cognitive Map (FCM) methodology. The proposed methodology concentrates its efforts on personalized/individual decision making including the family history and the demographic risk factors to elicit the hidden risk of developing breast cancer. Hebbian-based learning capabilities of FCM were used to improve the modeling issue and contribute to risk prediction. The accuracy of the system is compared with benchmark machine learning methods showing its superiority.